Pengaruh Aromaterapi Lavender Terhadap Penurunan Tingkat Nyeri Disminore Pada Siswi Kelas XII SMK Kesehatan Mulya Karya Husada Jagakarsa Tahun 2023 - Adinda Lisa Fikadila; Elvi Tresya; Indri Sarwili (Lembaga Pengembangan Kinerja Dosen, 2024)
Dysminorrhea is pain caused by spasm of the uterine muscles and increased levels of prostaglandins. Pain before or during menstruation is characterized by one of the symptoms that women often experience during menstruation, namely pain in the lower abdomen. Lavender aromatherapy is an alternative treatment method using lavender fragrance containing linalyl acetate which has a relaxing effect on the nervous and muscle systems, while linalool has a relaxing and sedative effect so it is used to relieve menstrual cramps. This study aims to determine the effect of lavender aromatherapy on reducing the level of dysmenorrhea pain in class The data collection method uses the Numeric Rating Scale (NRS) menstrual pain measurement questionnaire. The population in this study was 89 respondents and the sample was 20 respondents. The results showed that the average level of pain in female students before being given lavender aromatherapy was moderate pain, after being given lavender aromatherapy showed a mild level of pain, and the pain level before and after being given lavender aromatherapy had a p-value of 0.000 (<0.05) using the Wilcoxon Signed Rank T-test which states that Ha is accepted and Ho is rejected, it can be concluded that there is an effect of lavender aromatherapy on reducing the level of dysmenorrhea pain in class XII female students at Mulya Husada Jagakarsa Health Vocational School in 2023.